The Impact of Information and Communication Technology (ICT) on Marketing Performance in Islamic Banks: Empirical Evidence from Southern Jordan - Qwader, Amjad Salem Younes; Al-Rawashdeh, Eyad Taha; Al-Badaineh, Ghazy; Al-Oshaibat, Sulieman D. (International Review of Management and Marketing, 2025)
This study investigates the role of Information and Communication Technology (ICT) in enhancing marketing performance among Islamic banks in Southern Jordan, amidst the ongoing digital transformation within the banking sector. It aims to fill a critical research gap by examining how these technologies contribute to marketing improvements within the context of Islamic Sharia principles and an increasingly competitive environment. Adopting a descriptive-analytical methodology, primary data was collected through two structured questionnaires: one targeting 150 employees (senior management and IT specialists) using purposive sampling and the other targeting 150 customers who regularly use digital banking services, selected through simple random sampling. Data analysis was performed using SPSS (Version 26), incorporating statistical methods such as correlation coefficients, regression analysis, and ANOVA. The results reveal a statistically significant positive relationship between ICT adoption and marketing performance, with a correlation coefficient (R2 = 0.70) and a determination coefficient (R2 = 0.48), indicating that ICT explains 48% of the variance in marketing performance. Notably, there is a gap between employees’ and customers’ perceptions regarding ICT effectiveness, highlighting the need for improved digital communication and awareness initiatives. The study recommends sustained investment in digital infrastructure, targeted employee training programs, and AI-based, data-centric marketing tools to improve customer experiences, satisfaction and enhance competitiveness in the Islamic banking sector.